Public Sector Employment, Quality of Government, and Well-Being: A Global Analysis. (September 2021) - Davidson, Robert; Pacek, Alexander; Radcliff, Benjamin
While a growing literature within the study of subjective well-being demonstrates the impact of socio-political factors on subjective well-being, scholars have conspicuously failed to consider the role of the size and scope of government as determinants of well-being. Where such studies exist, the focus is largely on the advanced industrial democracies of the Organization for Economic Co-Operation and Development. In this study, we examine the size of the public sector as a determinant of cross-national variation in life satisfaction across a worldwide sample. Our findings strongly suggest that as the public sector grows, subjective well-being increases as well, conditional on the extent of quality of government. Using cross-sectional data on 84 countries, we show this relationship has an independent and separable impact from other economic and political factors.